HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG HIV/AIDS SERTA DUKUNGAN SUAMI DENGAN KESEDIAAN IBU DALAM MELAKUKAN VCT DI PUSKESMAS BALOI PERMAI KOTA BATAM. - Antika, Indah Amelia; Sihombing, Sarmauli Franshisca (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
A normal and healthy pregnancy is what every woman desires. Diseases experienced during pregnancy will be at risk for the baby. One of the most feared diseases is the Human Immunodeficiency Virus (HIV). The VCT strategy is at the core of all HIV / AIDS prevention and control efforts. Therefore, preventive service of HIV transmission from a mother to a child is one of the efforts to combat HIV and AIDS integrated with health services. The purpose of this study was to determine whether the Relationship between Knowledge of Pregnant Women and HIV / AIDS and the Support of Husbands in Their Willingness to Perform VCT. The research design used in this study was an Analytical Survey using the Cross Sectional approach. The study was conducted in April to August Â at the Public Health Center Baloi Permai in Batam. The population in this study was 273 respondents with a sample of 73 respondents, using a point time approach technique. Data collection using questionnaire instruments filled out by respondents. Data in tabular and textual form was analyzed using Chi-Square. The statistical test results obtained 66 respondents with good knowledge, husband less-support was 40 respondents and the willingness of pregnant women 73 respondents There is a significant relationship between Knowledge (p = 0,000) and husband support (p = 0.007) with the willingness of mothers to conduct VCT. It is expected to improve socialization about HIV / AIDS and VCT services at the Public Health Center and motivate health workers to play a role in increasing public knowledge about VCT testing through counseling in more creative ways. Hence, the community is interested in participating in these activities, and providing educative information so as to increase the knowledge of pregnant women related to VCT.